Organisational Legal Measures for Preventing Epidemics in Daugavpils and Rēzekne Districts in the 1860s and 1870s. - Petlina, Tetiana V. (Teisė, 2024)
The given article is dedicated to the topic of organizational-legal measures for combatting contagious diseases in the cities of Daugavpils (then Dinaburg) and Rēzekne (then Rezhytsa) in the 1860s and 70s, which is one of the earliest pages in the history of public health and epidemiology in Latvia. The author has grounded the given research upon the archival materials, upon which it was found that the said cities and their outskirts have survived a number of dangerous epidemics, which caused multiple victims. The legal foundation of the physicians’ and other officials’ activity in the field of combatting epidemics was the Doctor’s Statute (1857). The archival materials depicted that the aforementioned districts survived the epidemics of cholera in 1866, scarlet fever in 1876–1877, and smallpox in 1878–1879. The archival materials also illustrated that the physicians and other officials used to provide detailed reports on the epidemic situation within their respective districts, how they treated the patients and how they strived to find what was the cause of the epidemics. The reports of the district and town physicians frequently mentioned the lack of financial and material resources for combatting epidemics, as well as the lack of physicians, midwives, and paramedics in the appropriate districts, the necessity of district and village physicians to travel long distances for visiting patients and providing necessary medical assistance, as well as lack of swift communication and reporting between the physicians and other officials. It is also notable, that the diligence of the physicians was the key factor in combatting epidemic diseases since the district physicians played a pivotal role in safeguarding public health.
Keywords: public health; contagious diseases; history of epidemiology; legal history; public law; physician’s rights and duties